2004
DOI: 10.1016/j.neucom.2004.01.128
|View full text |Cite
|
Sign up to set email alerts
|

Spike-triggered characterization of excitatory and suppressive stimulus dimensions in monkey V1

Abstract: Neurons in primary visual cortex are commonly characterized using linear models, or simple extensions of linear models. Speciÿcally, V1 simple cell responses are often characterized using a rectiÿed linear receptive ÿeld, and complex cell responses are often described as the sum of squared responses of two linear subunits. We examined this class of model directly by applying spike-triggered covariance analysis to responses of monkey V1 neurons under binary white noise stimulation. The analysis extracts a low-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 11 publications
3
41
0
Order By: Relevance
“…Recently, several groups have shown that neurons in the primary visual cortex can be described as a set of spatiotemporal linear filters, and these underlying filters can be estimated by conducting a spike-triggered covariance (STC) technique (Touryan et al, 2002;Rust et al, 2004Rust et al, , 2005. The STC and LSRC analyses seem to share several desirable features, especially in that both of these techniques attempt to reveal filtering profiles underlying the responses of neurons and that both of them use white-noise sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups have shown that neurons in the primary visual cortex can be described as a set of spatiotemporal linear filters, and these underlying filters can be estimated by conducting a spike-triggered covariance (STC) technique (Touryan et al, 2002;Rust et al, 2004Rust et al, , 2005. The STC and LSRC analyses seem to share several desirable features, especially in that both of these techniques attempt to reveal filtering profiles underlying the responses of neurons and that both of them use white-noise sequences.…”
Section: Discussionmentioning
confidence: 99%
“…We define the "nonlinear RF" as the first principal component of the spike-triggered stimuli. This nonlinear RF has been used to describe the nonlinear properties of complex cells (see Rust et al 2004;Touryan et al 2002) (see also METHODS). Panels on the right of Fig.…”
Section: Linear Cellsmentioning
confidence: 99%
“…Recently developed data-analysis tools have provided new ways to characterize neurons that combine inputs nonlinearly (de Ruyter van Steveninck and Bialek 1988;Paninski 2003;Rust et al 2004; Schwartz et al 2001;Sharpee et al 2004;Simoncelli et al 2004;Touryan et al 2002). Here we use one of these techniques to reveal a surprising nonlinear computation performed by blue-yellow neurons in V1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Quadratic forms are used in experimental studies as quadratic approximations to the input-output function of neurons and can be derived from neural data as Volterra/Wiener approximations up to the second order [3][4][5][6][7][8][9][10][11][12][13] . In addition, several theoretical studies have defined quadratic models of neuronal RFs either explicitly 2,14,15 or implicitly as neural networks [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%